Early Pan-African magmatism in the Tarim Craton: Insights from zircon U-Pb-Lu-Hf isotope and geochemistry of granitoids in the Korla area, NW China - Ge, Rongfeng; Zhu, W.; Zheng, B.; Wu, H.; He, J.; Zhu, X. (Elsevier BV, 2012)
Extensive Neoproterozoic magmatism occurred in the Tarim Craton, providing a key to understanding the role of Tarim in the Rodinia and Gondwana supercontinents. We present LA-ICP-MS zircon U-Pb ages, Lu-Hf isotopic data and geochemical data of granitoids in the Korla area, northern Tarim Craton. These granitoids occur as plutons or dykes intruding into Paleoproterozoic high-grade metamorphic rocks and show minor evidence of deformation and metamorphism. Zircon U-Pb dating for three quartz syenite samples and two syenogranitic samples indicate that they were emplaced during two relatively short periods at ca. 660Ma and ca. 630Ma, respectively, which are broadly coeval with the intrusion of nearby mafic dykes. A melanosome and a leucogranite vein of banded migmatite from the nearby wall rock yield zircon ages of 658.9±3.4Ma and 634.9±3.4Ma, respectively, which probably record local partial melting and migmatization induced by coeval magma intrusion. Zircon eopen Hf(ap) for these rocks varies from -15.7 to +4.3, with a variation up to 10 epsilon Hf units for individual sample. This is ascribed to mixing of magmas sourced from depleted mantle and old continental crust. Geochemical data suggest that these granitoids are potassic and weakly peraluminous rocks and are variously enriched in LREE, K, Rb, Ba and depleted in Nb, Ta, Ti and P. It is suggested that these granitoids formed on a continental arc during its transition to a back-arc rift due to slab rollback. Considering the ca. 700Ma oceanic subduction and high-pressure metamorphism recorded by the Aksu blueschist, we infer that an early Pan-African retreating accretionary orogen was created along the northern Tarim Craton, which might be correlative with the northernmost East African Orogen. Combining with previous geochronological data, four magmatic episodes during the latest Mesoproterozoic-Neoproterozoic can be distinguished in Tarim: (1) ca. 1050-900Ma; (2) ca. 830-790Ma; (3) ca. 760-730Ma; (4) ca. 660-630Ma. The former three episodes probably recorded the assembly and breakup of Rodinia in Tarim, while the fourth probably documented the back-arc extension following the early Pan-African accretionary orogeny.